2011
DOI: 10.1118/1.3658572
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a newly proposed Monte Carlo based small field dosimetry formalism for a comprehensive set of diode detectors

Abstract: A number of general conclusions are evident: (1) small field OR(det) are very sensitive to the simulated source parameters, and therefore, rigorous Monte Carlo linac model commissioning, with respect to measurement, must be pursued prior to use, (2) backscattered dose to the monitor chamber should be included in simulated OR(det) calculations, (3) the corrections required for diode detectors are design dependent and therefore detailed detector modeling is required, and (4) the reported detector specific correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 40 publications
5
88
0
Order By: Relevance
“…Correction factors from the literature were applied to two of the results with the other result being uncorrected. The correction factors applied were from a range of sources and one was a weighted average from five different papers 10, 11, 13, 14, 15. The average of the reported output factors was 0.613 with a standard deviation of 2.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Correction factors from the literature were applied to two of the results with the other result being uncorrected. The correction factors applied were from a range of sources and one was a weighted average from five different papers 10, 11, 13, 14, 15. The average of the reported output factors was 0.613 with a standard deviation of 2.5%.…”
Section: Resultsmentioning
confidence: 99%
“…The overresponse in the diode measurements of our study is expected to be greater, due to the increased presence of lower energy photons because of the lack of flattening filter. Cranmer‐Sargison et al (11) also reported correction factors of SFD detector by using Monte Carlo simulation. MC simulations (EGSnrc) were benchmarked for the Varian Clinac iX 6 MV accelerator to determine kQitalicclin,Qitalicmsrfitalicclin,fitalicmsr correction factors for various diode detectors.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no machine‐specific correction factor for the SFD detector in this study, significant error may result if detector correction factors are not applied in small field dosimetry. This study averaged the SFD detector correction factors by Ralston et al (26) and Cranmer‐Sargison et al (11) resulting in 0.9395, 0.9655, 0.982, and 0.993 for 4 mm, 5 mm, 7.5 mm, and 10 mm cone, respectively. No correction factors were applied for cone size greater than and equal to 12.5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Monte Carlo calculated actor ΩQcline,Qmsrfclin,fmsr was recommended to correct the field factor. Several studies have been published since then to generate correction factors for various detectors from different treatment platforms 40 , 41 . The diodes were shown to have an overresponse at small fields.…”
Section: Discussionmentioning
confidence: 99%